Akuntansi Sebagai Alat Perencanaan - Doni Wirshandono Yogivaria (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to help stakeholders who use manual bookkeeping and introduce simple accounting as a planning concept in the future with Excel tools as program assistants. This study uses a research design. Analysis is used for system development in business processes, problem identification, and information needs analysis. The results achieved are the concept of recording purchases, receivables and cash disbursements to overcome the problems that exist in the company. The conclusion of the study is that the use of the Excel program can accelerate the financial process and minimize efficiency as well as the basis for further accounting programming as a planning tool in companies. Accounting is applied to basically all aspects of strategic management, so that accounting functions as a tool in strategic management.